Androgen deprivation therapy use and risk of death in men treated with high‐dose radiation for intermediate‐risk prostate cancer. Issue 15 (18th May 2016) - Keane, Florence K.; D'Amico, Anthony V.
Abstract : Men with favorable intermediate‐risk prostate cancer have excellent outcomes in comparison with men with unfavorable intermediate‐risk disease. In this issue of Cancer, Falchook et al report the largest study to date of men with favorable intermediate‐risk prostate cancer treated with dose‐escalated radiotherapy with or without androgen deprivation therapy. They demonstrate that overall survival is not associated with the use of androgen deprivation therapy and provide level 2 evidence to suggest the exclusion of androgen deprivation therapy in this population. See also pages 2341–9.